Pelatihan Penyusunan Laporan Keuangan Terhadap Wirausaha UMKM di Tegal Alur, Jakarta Barat - Ayu Oktaviani; Vinola Herawaty (Penerbit Goodwood, 2022)
Purpose: To improve financial management in entrepreneurship for MSME entrepreneurs, especially in the preparation of financial reports (covering the meaning, objectives, benefits, types, and components in financial reports) and to increase and understanding of knowledge in preparing financial reports. Method: The method used are counselling and training about preparing the financial reports for MSME entrepreneurs located in the Tegal Alur Village area. This activity was carried out in collaboration with the Faculty of Economics and Business, Trisakti University with MSMEs in the Tegal Alur Village Area, Kalideres District, West Jakarta. Result: This training has been carried out well and successfully on April 14, 2022 via online. The results achieved by the participants are: (1) Participants have understood the importance of business financial reports and their benefits, (2) Participants have understood with the components in each financial report, and (3) Participants have known examples of good financial reports. Conclusion: Although most of the participants have made financial reports, so far they are not sure whether their reports are in accordance with applicable accounting rules and reporting standards. The resulting financial reports are still limited to reports showing the profit or loss of business activities. Participants still need guidance and assistance in preparing financial reports, especially statements of financial position and notes to financial statements in accordance with SAK EMKM.